A conceptual service oriented architecture framework for integrated flood management - Hamzah, M. H. I.; Baharom, Fauziah; Hussain, Azham (2014)
Service oriented architecture (SOA) is a platform and language-independent that guide different services to work together in order to perform business process.The benefits of using SOA such as interoperability, discoverability, loose coupling, flexibility and reliability have led previous researchers to use it as their fundamental basis in designing their software architecture framework.Previous researchers also have exploit SOA and implement it into flood management domain to manage the complex systems that are distributed across the network.However, previous works do not provide the detail process of emergency management into their flood management framework.Therefore, this study aims to propose a conceptual SOA framework for an integrated flood management (IFM) in order to increase the effectiveness and efficiency of managing flood.Furthermore the feasibility of using SOA and the required process of flood management in order to construct the conceptual framework are being investigated by means of a comparative study.In addition, this study also suggests the Service oriented architecture Modeling Language (SoaML) as a technique to model the services for anIFM.